2018
DOI: 10.1177/0003702818812090
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell and Bulk Fluorescence Excitation Signatures of Seven Phytoplankton Species During Nitrogen Depletion and Resupply

Abstract: Phytoplankton play a vital role as primary producers in aquatic ecosystems. One common approach to classifying phytoplankton is fluorescence excitation spectroscopy, which leverages the variation in types and concentrations of pigments among different phytoplankton taxonomic groups. Here, we used a fluorescence imaging photometer to measure excitation ratios (''signatures'') of single cells and bulk cultures of seven differently pigmented phytoplankton species as they progressed from nitrogen N-replete to N-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Furthermore, because we used a broad light spectrum and PUR is scaled to the amount of light available at each wavelength, we can be confident that all of our strains had available to them the light that they could capture, and that PUR measurements were not phylogenetically biased. Because phenotypic plasticity of cellular concentrations of photopigments with respect to light and nutrients is known [62,63,77], future work on the relationship between pigment characteristics and light capture as resource acquisition would benefit from a reaction norm approach that considers more environments. Such a strategy potentially resolves the trade-off between environment-specific and common-garden phylogenetic comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because we used a broad light spectrum and PUR is scaled to the amount of light available at each wavelength, we can be confident that all of our strains had available to them the light that they could capture, and that PUR measurements were not phylogenetically biased. Because phenotypic plasticity of cellular concentrations of photopigments with respect to light and nutrients is known [62,63,77], future work on the relationship between pigment characteristics and light capture as resource acquisition would benefit from a reaction norm approach that considers more environments. Such a strategy potentially resolves the trade-off between environment-specific and common-garden phylogenetic comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…The fluorescence of the chlorophyll-based reaction centers, photosystem I and photosystem II, has been the basis for detecting chlorophyll and, by extension, phytoplankton in water for many years 9 and our laboratories have previously used fluorescence for phytoplankton analysis. 10,11…”
Section: Introductionmentioning
confidence: 99%
“…The fluorescence of the chlorophyll-based reaction centers, photosystem I and photosystem II, has been the basis for detecting chlorophyll and, by extension, phytoplankton in water for many years 9 and our laboratories have previously used fluorescence for phytoplankton analysis. 10,11 Fluorescence is a useful tool for in situ analysis of phytoplankton in water, but in situ methods are not likely to soon replace laboratory analysis based on water sampling. This is because a laboratory can bring to bear many tools for analyzing the number density and speciation of phytoplankton and can also provide correlating information on the nutrient conditions and chemical composition of water, the presence of bacteria and viruses, and other factors that are difficult to measure using in situ methods.…”
Section: Introductionmentioning
confidence: 99%
“…The herein described method demands no phycological expert knowledge, once a single-cell profiling database is established, ideally as an open-source repository. Since only cultures in well-defined conditions have been investigated, future studies will implement various stress conditions, as those were shown to have a strong influence on the metabolic profile of a microalgal cell (Faulkner et al 2019;Driver et al 2015). The present approach that monitors the metabolome has the potential to generate data about the physiological state of the single cells and thus about the metabolic heterogeneity of a plankton population.…”
Section: Resultsmentioning
confidence: 99%